INFLUENCE OF CLIMACTERIC SYMPTOMATOLOGY ON THE SEXUAL FUNCTION OF PANKARARU INDIGENOUS WOMEN - Nogueira, Aécio Menezes; de Souza, Pedro Henrique Nogueira; de Campos, Edemilson Antunes; de Souza , Claudinalle Farias Queiroz; da Costa , Aurélio Molina (Seven Editora, 2024)
Objectives: The aim of this study was to explore the statistical association between climacteric symptoms and sexual function in women of the Pankararu ethnic group.Study design: A cross-sectional descriptive study was carried out with 188 indigenous women, aged between 35 and 65 years, for which a sample of 108 women who met the inclusion and exclusion criteria was obtained, and answered all three questionnaires: one socioeconomic and demographic, the Menopause Rating Scale (MRS) and the Sexual Quotient-female version (SQF). The study site was the municipalities of Tacaratu and Petrolândia, Pernambuco State, Brazil, during the months of August and September 2019. Main outcome measures: Assessment of the intensity of climacteric symptomatology and the overall quality of sexual performance/satisfaction.Results: The mean age was 44.4 years, with the majority (72.2%) between 35 and 49 years. The prevalence of climacteric symptoms was high (67.6%), with intensity directly associated with age. The most intense symptoms included physical and mental exhaustion (16.7%), shortness of breath, sweating and hot flashes (13.0%) and muscle and joint problems (12.0%). In sexual function, 51.9% achieved a score indicative of female sexual dysfunction and 35.2% of the women were categorized as having poor or unfavorable performance/satisfaction and inversely associated with age, with the worst being in the foreplay sexual and comfort domains.Conclusions: The prevalence of climacteric symptoms was high among the indigenous women studied, with increasing intensity with age and inversely associated with satisfactory sexual performance/satisfaction, indicating an association between advancing age, increased climacteric symptoms and reduced quality of sexual function. DOI:https://doi.org/10.56238/sevened2024.037-021